pH Condition Influence Nanotube Structure of TiO2 by Anodizing Titanium Substrate / Nur Aimi Jani… [et al.] - Jani, Nur Aimi; Azizan, Izzatul Syifa; Razak, Nur Fatin; Mahat, Mohd Muzamir; Chiu, Weesiong; Abdul Rahman, Saadah (Faculty of Applied Sciences, 2020)
The influence of pH of the electrolyte used during anodization of Titanium substrate has been investigated in order to determine the optimum pH condition to form self-organized Titanium dioxide (TiO2) nanotubes (NTs) structure. The TiO2 NTs was formed by anodizing Titanium substrate in an electrolyte containing 1M of sodium sulfate (Na2SO4) with 0.7 g of ammonium fluoride (NH4F) for 180 minutes with potential 20 V. The optimum conditions were determined by characterization using FESEM and XRD analysis. As shown in the result, it can be summarized that pH of the anodization electrolyte can affect the length and diameter of the NTs as confirmed by FESEM images. FESEM result shows that, the length of nanotubes increased as the pH increased which are from 50 nm to 424 nm for pH 5 and pH 7, respectively. However, at higher pH more than 7, the nanotube structure was collapsed and only form bulk oxide film. The FESEM result also supported by the XRD result as the peak at 24° increased up from pH 3 to pH 7 and drop at pH 9.